Radiation therapy before radical cystectomy combined with immunotherapy in locally advanced bladder cancer – study protocol of a prospective, single arm, multicenter phase II trial (RACE IT) - Sebastian C. Schmid; Florestan J. Koll; Claus Rödel; Philipp Maisch; Andreas Sauter; Franziska Beckert; Anna Seitz; Hubert Kübler; Michael Flentje; Felix Chun; Stephanie E. Combs; Kilian Schiller; et al. (BMC Cancer, 2020)
Abstract Background Patients with locally advanced bladder cancer (cT3/4 cN0/N+ cM0) have a poor prognosis despite radical surgical therapy and perioperative chemotherapy. Preliminary data suggest that the combination of radiation and immunotherapy does not lead to excess toxicity and may have synergistic (abscopal) anti-tumor effects. We hypothesize that the combined preoperative application of the PD-1 checkpoint-inhibitor Nivolumab with concomitant radiation therapy of the bladder and pelvic region followed by radical cystectomy with standardized lymphadenectomy is safe and feasible and might improve outcome for patients with locally advanced bladder cancer. Methods Study design: “RACE IT” (AUO AB 65/18) is an investigator initiated, prospective, multicenter, open, single arm phase II trial sponsored by Technical University Munich. Study drug and funding are provided by the company Bristol-Myers Squibb. Study treatment: Patients will receive Nivolumab 240 mg i.v. every 2 weeks for 4 cycles preoperatively with concomitant radiation therapy of bladder and pelvic region (max. 50.4 Gy). Radical cystectomy with standardized bilateral pelvic lymphadenectomy will be performed between week 11–15. Primary endpoint: Rate of patients with completed treatment consisting of radio-immunotherapy and radical cystectomy at the end of week 15. Secondary endpoints: Acute and late toxicity, therapy response and survival (1 year follow up). Main inclusion criteria: Patients with histologically confirmed, locally advanced bladder cancer (cT3/4, cN0/N+), who are ineligible for neoadjuvant, cisplatin-based chemotherapy or who refuse neoadjuvant chemotherapy. Main exclusion criteria: Patients with metastatic disease (lymph node metastasis outside pelvis or distant metastasis) or previous chemo-, immune- or radiation therapy. Planned sample size: 33 patients, interim analysis after 11 patients. Discussion This trial aims to evaluate the safety and feasibility of the combined approach of preoperative PD-1 checkpoint-inhibitor therapy with concomitant radiation of bladder and pelvic region followed by radical cystectomy. The secondary objectives of therapy response and survival are thought to provide preliminary data for further clinical evaluation after successful completion of this trial. Recruitment has started in February 2019. Trial registration Protocol Code RACE IT: AB 65/18; EudraCT: 2018–001823-38; Clinicaltrials.gov: NCT03529890; Date of registration: 27 June 2018.